Change, Choice, and Commercialization: Backpacker Routes in Southeast Asia. (2nd February 2016) - Hampton, Mark P.; Hamzah, Amran
Abstract: Southeast Asia has the world's oldest and largest backpacker trails. This paper examines the geographies of such flows, drawing upon the largest survey to date of backpackers in Asia using qualitative research to survey the key changes from the 1970s to the 2000s. Backpacker trails have changed significantly and new routes have emerged including the "northern trail" (Bangkok–Cambodia–Vietnam–Laos). It is to be expected that routes change as backpackers constantly seek new places, pioneering for later mass tourism. However, this paper suggests that using institutionalization as a framework, these changing trails and backpacker "choices" can be seen as driven by growing commercialization and institutionalization. This then operates in combination with external variables (travel innovations—low cost airlines, and new transport networks); exogenous shock (political instability, terrorism); and growing regional competition from emerging destinations such as Vietnam and Cambodia.